2014
DOI: 10.1176/appi.ps.201200247
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Implementing Evidence-Based Smoking Cessation Practices in Nine Community Mental Health Sites

Abstract: Mental health clinicians working in community mental health settings were not consistently providing evidence-based smoking cessation interventions. Barriers appear to be modifiable through training and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 37 publications
1
85
0
1
Order By: Relevance
“…NRT is an evidence-based treatment for tobacco dependence [32,35], and its effectiveness and safety among behavioral health consumers have been demonstrated [19]. TTTF provided Spindletop a supply (total value of US$15,365) of NRTs (14 and 21 mg nicotine patches and 4 mg nicotine gum) to be distributed among consumers and staff.…”
Section: Component B: Basic Tobacco Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…NRT is an evidence-based treatment for tobacco dependence [32,35], and its effectiveness and safety among behavioral health consumers have been demonstrated [19]. TTTF provided Spindletop a supply (total value of US$15,365) of NRTs (14 and 21 mg nicotine patches and 4 mg nicotine gum) to be distributed among consumers and staff.…”
Section: Component B: Basic Tobacco Educationmentioning
confidence: 99%
“…tobacco users with BHD [19][20][21][22]. Adding TUAs to a healthcare setting's electronic health record (EHR) has been shown to increase the identification and treatment of tobacco users [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, previous research (Blasinsky et al, ; Gruen, Riddle, & Goldman, ) has found demonstration of positive outcomes to be a driver for sustainment of interventions, and some NPT‐based studies also suggest this is important for normalisation (Coupe, Phaff, & Nieboer, ; Lloyd, Joseph‐Williams, Edwards, Rix, & Elwyn, ). From the perspective of NPT, generating information of effectiveness during implementation and sustainment can be an important activity of reflexive monitoring since this may enhance the coherence and cognitive participation of the participants (provided that the effects are positive).…”
Section: Discussionmentioning
confidence: 92%
“…However, smoking rates for BHCs remain relatively static, and significantly higher, at 35.8% [9]. Practice guidelines [2,10,11] recommend that smokers with and without behavioral challenges receive the same evidencebased-practices (EBPs) [12] proven effective in helping individuals in both groups to successfully quit smoking [13,14] at the same rates [15,16]. Nonetheless, BHCs are less likely to quit smoking compared to those in the general population [1,3] despite research showing equally high motivation to quit among both groups [17][18][19].…”
Section: Introductionmentioning
confidence: 99%